Jilbab sebagai Identitas Organisasi Islam di Perguruan Tinggi - Qowim Musthofa (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
This article was written based on research into jilbab (veil) wearing practices in the Muslim Student Organization KAMMI (Indonesian Muslim Student Action Unit), IMM (Muhammadiyah Student Organization), and KMNU (Nahdlatul Ulama Student Family) Yogyakarta. This study uses qualitative methods by conducting in-depth interviews. The approach is psychological-phenomenological. The principal argument of this study, the veil is used not only the theological issues and commitment to the organization, but also because of the search process that is influenced by psychological aspects.It finds that wearing of the jilbab is a process of identity formation, with individual students being influenced by their intellectualdevelopment, accumulated experiences, and psycho-social situation.